2019
DOI: 10.1016/j.heliyon.2019.e01912
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photocatalytic activity against crystal violet dye of Co and In doped ZnO thin films grown on PEI flexible substrate under UV and sunlight irradiations

Abstract: This work is focused on the photocatalytic activities of undoped ZnO, Co (1%) doped ZnO (CZO) and In (1%) doped ZnO (IZO) thin films grown on flexible PEI (Polyetherimide) substrate by spray pyrolysis. The photodegradation of crystal violet dye was investigated under UV and sunlight irradiations. Doping and excitation energy effects on photocatalytic efficiencies are discussed. All ZnO thin films show high photocatalytic efficiency up to 80% under either UV or sunlight irradiations for 210 min. However, CZO ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Firstly, we note a decrease in PL intensity, indicating that Ce doped ZnO has a low electron-hole recombination rate. 61,62 Thus, ZnO may exhibit better photocatalytic activity than Ce-ZnO under UV irradiation. Overall, data shows that introducing cerium into the structure of zinc oxide decreases ZnO's photocatalytic effectiveness under UV light, instead signicantly increasing the photocatalytic efficiency under visible light.…”
Section: Drs and Pl Resultsmentioning
confidence: 99%
“…Firstly, we note a decrease in PL intensity, indicating that Ce doped ZnO has a low electron-hole recombination rate. 61,62 Thus, ZnO may exhibit better photocatalytic activity than Ce-ZnO under UV irradiation. Overall, data shows that introducing cerium into the structure of zinc oxide decreases ZnO's photocatalytic effectiveness under UV light, instead signicantly increasing the photocatalytic efficiency under visible light.…”
Section: Drs and Pl Resultsmentioning
confidence: 99%
“…The reproducibility of the photocatalytic experiments is confirmed and observed very clearly through the 20 photodegradion cycles. Ben Ameur et al [83] have conducted many cycles of thin film of ZnO: Co (1%) doped ZnO (CZO), and In (1%) doped ZnO (IZO). Their measurements clearly showed that after three cycles, the photo-degradation remains almost constant with a deactivation not exceeding (11%).…”
Section: Reusability and Photo-stability Of The Catalyst For The Bina...mentioning
confidence: 99%
“…Quite interestingly, they obtained better photocatalytic activities for their In doped ZnO nanostructures containing rich oxygen vacancy defects under visible light irradiation towards the degradation of methylene blue (MB) and methyl orange (MO) corresponding to 96.84% and 90.05%, respectively. S. B. Ameur et al grew thin films of undoped ZnO, (1%) Co doped ZnO and (1%) In doped ZnO on flexible PEI (Polyetherimide) substrate via spray pyrolysis [40]. They observed that undoped as well as Co and Indoped ZnO thin films exhibited Photocatalytic efficiency against crystal violet dyeup to 80% under either UV light or sunlight when irradiated for 210 min.…”
Section: Photocatalytic Studymentioning
confidence: 99%
“…photocatalytic degradation of organic compounds but very few reports are available on photocatalytic hydrogen generation[36][37][38][39][40]. M.G.…”
mentioning
confidence: 99%